2014
DOI: 10.1093/jxb/eru164
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene, MdSSK1, as a component of the SCF complex rather than MdSBP1 can mediate the ubiquitination of S-RNase in apple

Abstract: SummaryThe related components of the SCF complex in apple were cloned and it was proved that an SCF complex containing MdSSK1 rather than MdSBP1 can mediate the ubiquitination of S-RNase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…Nevertheless, the possible involvement of SBP1 in SI is still unclear because SBP1 by itself was reported to interact with S-RNase in the family Solanaceae and the tribe Maleae Kao, 2006, 2008;Minamikawa et al, 2013;Sims and Ordanic, 2001). Furthermore, polyubiquitination of S-RNase by SBP1 was observed in vitro in Solanaceae species, while no such polyubiquitination was detected in Maleae species Kao, 2006, 2008;Yuan et al, 2014).…”
Section: Molecular Mechanism Of Self/nonself Discrimination By Multipmentioning
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, the possible involvement of SBP1 in SI is still unclear because SBP1 by itself was reported to interact with S-RNase in the family Solanaceae and the tribe Maleae Kao, 2006, 2008;Minamikawa et al, 2013;Sims and Ordanic, 2001). Furthermore, polyubiquitination of S-RNase by SBP1 was observed in vitro in Solanaceae species, while no such polyubiquitination was detected in Maleae species Kao, 2006, 2008;Yuan et al, 2014).…”
Section: Molecular Mechanism Of Self/nonself Discrimination By Multipmentioning
confidence: 91%
“…Although SBP1 was also identified in the tribe Maleae, inconsistent results were obtained regarding the interaction between SBP1 and SFBB. Minamikawa et al (2014) observed that SBP1 interacted with SFBB and Cul1, which contradicted the findings of Yuan et al (2014). Nevertheless, the possible involvement of SBP1 in SI is still unclear because SBP1 by itself was reported to interact with S-RNase in the family Solanaceae and the tribe Maleae Kao, 2006, 2008;Minamikawa et al, 2013;Sims and Ordanic, 2001).…”
Section: Molecular Mechanism Of Self/nonself Discrimination By Multipmentioning
confidence: 95%
See 2 more Smart Citations
“…The isopropyl b-D-1-thiogalactopyranoside concentration for inducing protein expression was 0.5 mM, and the purification of the GST-or His-tagged fusion proteins was performed as previously described (Li et al, 2016). The purification of the MBP-tagged fusion protein was performed as by Yuan et al (2014). All primers used are listed in Supplemental Data Set 1.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%